Biostimulant and vegetable extract use on millet under saline stress (Research, Society and Development, 2020)
Millet (Pennisetum glaucum) is a species considered moderately tolerant to salinity. The objective of this study was to evaluate the influence of a commercial biostimulant (ACADIAN) and the vegetable extract (Cyperus rotundus) on growth and forage production of millet submitted to saline stress conditions. The experiment was carried out in a randomized complete block in a 3x4 factorial scheme composed of biostimulant, nutsedge extract and control in four levels of irrigation water salinity (0, 1, 2 and 4 dS m-1), with four replications. The study was conducted in the Federal Rural University of Pernambuco, Academic Unit of Serra Talhada, located in Serra Talhada, from January 30, 2017 to April 5, 2017. In the salinity absence, the nutsedge extract and the biostimulant promoted increases of 98 g DM vase-1 and 22 g DM vase-1 of millet aerial part, respectively. There was no specific response pattern for increasing the concentration of irrigation water salts in any of the analyzed variables, evidencing the tolerance of the specie to the salinity levels. The use of nutsedge extract and biostimulant favored the higher forage yield of millet.